EFFECTS OF ARTIFICIAL INTELLIGENCE ON HUMAN RESOURCES MANAGEMENT A STUDY OF IT SECTOR IN PAKISTAN - Tahira, Khushnooda (International Journal of Online and Distance Learning, 2021)
Purpose: The study examined effects of artificial intelligence on human resources management a study of it sector in Pakistan Methodology: The tool used for the purpose of gathering the data for this thesis was a questionnaire The content of the questionnaire had to be necessarily validated by a PhD professor .In order to fulfill the need of the research of finding out the relationship, which might exist between the given dependent and independent variables, correlation analysis was conducted using SPSS.. The research was also based upon facts and arguments based on the non-numerical data which is gathered through different articles. The respondents chosen for filling the research questionnaire were selected from the top ranking IT companies of Pakistan because of the fact that these companies, some of them being multi-national, would have the understanding of the modern challenges related to technology and the complexities of the recruitment. Result: Technology is the main focus of the whole world today. Companies who wish to survive in the modern industry must make their recruitment processes digitized by incorporating the modern technology so that not only the processes can be made faster but also their performance can be made better. Unique contribution to theory and practice: Artificial intelligence is the result of the modern world of complexities and new technological advancements which have allowed new entrant to enter new markets anytime. The biggest challenge of artificial intelligence is that it has made everything quick. Recruiters want to be catered quickly for this purpose, companies ought to have highly responsive HR system so that the hiring is on time